2021
DOI: 10.1038/s41419-021-04265-8
|View full text |Cite
|
Sign up to set email alerts
|

GOLPH3/CKAP4 promotes metastasis and tumorigenicity by enhancing the secretion of exosomal WNT3A in non-small-cell lung cancer

Abstract: Cancer metastasis is the main cause of mortality associated with non-small-cell lung cancer (NSCLC), accounting for up to 70% of deaths among patients. The mechanisms underlying distal metastasis remain largely unknown. Golgi phosphoprotein 3 (GOLPH3) correlates negatively with overall survival in multiple tumors. In this study, we evaluated the function of GOLPH3 in NSCLC distal metastasis. GOLPH3 was expressed at high levels in samples from patients with NSCLC and was positively associated with clinicopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Similar results were recently obtained by Song et al 62 in the context of Wnt3A. In their work, the authors studied NSCLC, showing that GOLPH3 overexpression enhances the cell migration and invasion abilities of NSCLC cells.…”
Section: The Role Of Golph3 In Proteins Excretion In Cancersupporting
confidence: 85%
“…Similar results were recently obtained by Song et al 62 in the context of Wnt3A. In their work, the authors studied NSCLC, showing that GOLPH3 overexpression enhances the cell migration and invasion abilities of NSCLC cells.…”
Section: The Role Of Golph3 In Proteins Excretion In Cancersupporting
confidence: 85%
“…Many studies have indicated that IL-17 is upregulated in a variety of cancer tissues and attributed to cancer cell proliferation, metastasis, and so on. [40][41][42] Despite it has been reported that NSCLC metastasis is the major reason for patient death, 43 and the elevation of IL-17 can induce NSCLC metastasis through p38 MAPK or nuclear factor-κB/ ZEB1 activation, 13,14 the exact mechanism for IL-17-triggered NSCLC metastasis is still not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GOLM1 can control colitis and colon tumorigenesis by regulating the balance of Notch signaling in the intestine ( 10 ). Golgi phosphoprotein 3 (GOLPH3) is involved in cell migration, GA morphology and orientation, and protein glycosylation, and the increased expression of GOLPH3 observed in a variety of tumors enhances cis-transport of GA and leads to increased cytosolic ejection of pro-metastatic factors such as cytokines, growth factors, and Wnt molecules ( 11 , 12 ). In addition, GA can enhance the secretion of immune factors and promote the formation of an immunosuppressive tumor microenvironment that promotes tumor progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%